Production of Protein Hydrolysates from Spent Coffee Grounds via Microwave, Enzymatic, and Subcritical Water Extractions and Their Combination - Panusorn Hunsub; Somkiat Ngamprasertsith; Nattapong Prichapan; Winatta Sakdasri; Aphichart Karnchanatat; Ruengwit Sawangkeaw (My University, 2023)
Spent coffee grounds (SCGs) are currently considered abandoned landfill waste despite retaining valuable organic compounds, especially with a high protein content of 16.64 ± 0.13 g/g dried SCGs and a high oil content of 15.48 ± 0.17 g/g dried SCGs. As a result, SCGs could serve as a potential source of valuable ingredients. However, utilizing a single technical strategy of alternative green extractions was insufficient for extracting the target compounds and hydrolyzing proteins. This work aimed to optimize the operating parameters of enzyme-assisted extraction (EAE), microwave-assisted extraction (MAE), and subcritical water extraction (SWE) using a response surface methodology. The results showed that EAE, at a papain-to-substrate ratio (E/S) of 0.5 and a duration of 15 min, generated a %DH of 93.39% and provided a water soluble protein concentration (WSPC) in the range of 400 to 800 µg/mL. Moreover, MAE provided a maximum %DH of 9.72% at 600 watts and 10 min, while SWE produced a maximum %DH of 13.41% at 160 °C in 17.5 min. However, the WSPCs of MAE and SWE extracts were comparable at ~250 µg/mL. The combination MAE−SWE enhanced the %DH of hydrolysates by more than the combined SWE−MAE, SWE, and MAE. However, the effects of differential hydrolysis on bioactivity are not directly correlated with %DH. In this study, the highest antioxidant activity was found at an E/S of 0.5 and in 15 min for EAE, at 350 W and in 10 min for MAE, and at 160 °C and in 30 min for SWE. This work demonstrated that the valorization of SCGs not only reduces the amount of waste but also yields functional cosmeceutical and nutraceutical ingredients.
Keywords: Water extraction; Coffee research and impacts